Circulating asymmetric dimethylarginine and cognitive decline: A 4‐year follow‐up study of the 1936 Aberdeen Birth Cohort. (8th June 2020) - Malden, Deborah E.; Mangoni, Arduino A.; Woodman, Richard J.; Thies, Frank; McNeil, Chris; Murray, Alison D.; Soiza, Roy L.
Abstract : Background: The underlying mechanisms leading to dementia and Alzheimer's disease (AD) are unclear. Asymmetric dimethylarginine (ADMA), an endogenous inhibitor of nitric oxide synthase, may be associated with cognitive decline, but population‐based evidence is lacking. Methods: Change in cognitive performance was assessed in participants of the Aberdeen Birth Cohort of 1936 using longitudinal Raven's progressive matrices (RPM) between 2000 and 2004. Multiple linear regression was used to estimate the association between ADMA concentrations in 2000 and change in cognitive performance after adjustment for potential confounders. Results: A total of 93 participants had complete information on cognitive performance between 2000 and 2004. Mean plasma ADMA concentrations were approximately 0.4 μmol/L lower in those participants with stable or improved RPM scores over follow‐up compared with participants whose cognitive performance worsened. In confounder‐adjusted analysis, one SD (0.06 μmol/L) increase in ADMA at 63 years of age was associated with an average reduction in RPM of 1.26 points (95% CI 0.14‐2.26) after 4 years. Conclusion: Raised plasma ADMA concentrations predicted worsening cognitive performance after approximately 4 years in this cohort of adults in late‐middle age. These findings have implications for future research, including presymptomatic diagnosis or novel therapeutic targets for dementia and AD.